Analisis Faktor yang Mempengaruhi Pemanfaatan Pelayanan Kesehatan Pada Peserta BPJS Penerima Bantuan Iuran (PBI) di Kota Binjai - Dhea Salsabila Br. Sitepu; Listi Tri Syafira; Fitriani Pramita Gurning (Lembaga Pengembangan Kinerja Dosen, 2025)
Contribution Assistance Recipients (PBI), namely people whose contributions are covered by the government because they are classified as underprivileged. This proportion shows the state's commitment to guaranteeing social protection in the health sector, especially for vulnerable groups. The objective of this study was to analyze the factors that influence the utilization of health services for BPJS Contribution Assistance Recipients (PBI) in Binjai City. This study used quantitative research with a cross-sectional approach design. The population in this study were all BPJS Contribution Assistance Recipients (PBI) participants in Binjai City who had used health service facilities with a total of 84,224 people and were willing to be respondents with a total of 382 respondents. The number of samples was determined by the Lemeshow formula. Based on the results of research conducted on BPJS Contribution Assistance Recipient (PBI) participants in Binjai City with a total of 382 respondents, the factors that significantly influence the utilization of health services for BPJS PBI participants are participant knowledge about health services, availability of health services, access to health services, support from BPJS health officers. The conclusion of this study confirms the importance of efforts to improve education and counseling for BPJS PBI participants so that they have positive knowledge and attitudes towards health services. In addition, improving the service system, including the availability of facilities, ease of access, and improving the quality of service and support from BPJS officers, are the main keys to increasing the use of health services.